Penerapan Marketing MIX Dalam Meningkatkan Penjualan JAS Laboratorium - Ida Ayu Triana; Dety Mulyanti (International Forum of Researchers and Lecturers, 2023)
Business in the field of selling laboratory coats is intended to make it easy for analysts and student analysts to obtain laboratory coats, with good quality and affordable prices. Marketing mix is very important in the current situation where trade competition is getting tighter. With the marketing mix, we can find out the elements of the lab coat business in more detail. The method used in this research is literature study, namely by searching various written sources, both in the form of journals, archives, magazines, books, articles, and relevant documents so that the information obtained from the literature study is used as a reference. to strengthen existing arguments. Sales of laboratory coats must provide quality products at affordable prices. The application of mix marketing aims to maintain and optimize product quality, obtain competitive prices in the market, increase sales onset and increase the number of customers.